Evaluation of the Factors Affecting of Epistaxis: A Study in a Tertiary Care Hospital, Dhaka. (Medicine Today, 2023)
Introduction: Epistaxis refers to the occurrence of bleeding from the nose or nasal cavity. It is widely recognized as one of the most common emergencies encountered in medical settings, particularly in the ear, nose, and throat departments, as well as in accident and emergency departments across the globe. The management of epistaxis depends on the severity of the bleeding and may involve various interventions, including conservative measures like nasal packing, cauterization techniques, or, in more severe cases, surgical interventions.Objective: The primary goal of this study was to investigate the various causes of epistaxis.Materials and Methods: This cross-sectional observational study was conducted at the Department of Otolaryngology and Head-Neck Surgery (ENT) in City Medical College & Hospital from May 2021 to April 2023. The study involved 220 patients who presented with epistaxis complaints at the ENT Outpatient Department or Emergency unit of hospital. Diagnosis of the cases was based on their medical history, clinical examination, radiological and laboratory investigations.Result: 220 patients were studied during the period. The mean age ± standard deviation was determined to be 36.67 ± 18.06 years. The age range spanned from 1 to 85 years. Patients less than 25 years old were 124 (56.36%) and more than 25 years old were 96 (43.74%). Males (139) predominated in both indoor and outdoor patients with a male-to-female ratio of 1.7:1. The nasal cavity most involved was left 103 (47%) compared to right 85 (38.6%). Bilateral involvement was seen in 32 (14.4%) cases. Higher incidence was also noticed during winters 93 (42.1%), followed by summer 63 (28.7%), then autumn 38 (17.2%), and least in spring 26 (11.9%). The circadian rhythm was also noted where we found epistaxis to be more during night 82 (37.6%), followed by evening 78 (35.3%), and finally morning 60 (27.1%). Previous history of hypertension (HTN) is seen in 26.3% of cases (58). The history of taking medications with hemorrhagic risk currently or stopped within the last 10 days was 3.5% (8). We also found a relationship between the age group ( 25 years) and the type of treatment.Conclusion: Epistaxis, or nosebleeds, can be caused by various factors such as trauma, inflammation, tumors, blood disorders, cardiovascular issues, and foreign bodies. Younger individuals are more prone to traumatic causes, while older individuals may experience more severe nosebleeds. Hypertension is a significant contributor, emphasizing the importance of blood pressure management. Understanding these diverse causes is crucial for effective treatment and prevention of potential complications.Medicine Today 2023 Vol.35(2): 124-128